2007
DOI: 10.1111/j.1478-3231.2007.01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic portosystemic encephalopathy in cirrhotic patients by embolization of portosystemic shunts

Abstract: We believe that optimal management of these patients with chronic spontaneous encephalopathy is liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 18 publications
(33 reference statements)
0
45
0
4
Order By: Relevance
“…Several authors have reported the safety and efficacy of transcatheter embolization of portosystemic shunts in patients with refractory HE [13,[32][33][34][35][36][37][38]. In addition, in the previous 10 years, many case reports on HE due to portosystemic shunts that were successfully treated by transcatheter embolization have been published [17][18][19][20][21][22][23][39][40][41][42].…”
Section: Efficacy and Safety Of Transcatheter Embolizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Several authors have reported the safety and efficacy of transcatheter embolization of portosystemic shunts in patients with refractory HE [13,[32][33][34][35][36][37][38]. In addition, in the previous 10 years, many case reports on HE due to portosystemic shunts that were successfully treated by transcatheter embolization have been published [17][18][19][20][21][22][23][39][40][41][42].…”
Section: Efficacy and Safety Of Transcatheter Embolizationmentioning
confidence: 99%
“…In addition, shunt occlusion leading to a rapid increase in portal pressure may induce serious complications, such as variceal bleeding and intractable ascites [13]. Thus, contraindications for transcatheter embolization include not only severe hepatic failure, but also uncontrolled variceal bleeding, refractory ascites, and severe coagulopathy.…”
Section: Indications and Contraindications Of Transcatheter Embolizationmentioning
confidence: 99%
See 3 more Smart Citations